PERAN PUSAT PELATIHAN SENI BUDAYA (PPSB) JAKARTA SELATAN DALAM REPRODUKSI KESENIAN GAMBANG KROMONG - Suseno, Dava Widyanti; Mulyana, Aton Rustandi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Along with the development of the capital city, the Betawi people and their culture have faced various challenges related to their identity and existence as “natives”. This condition has had a lot of influence on the condition where traditional arts are no longer alive and developing, one of which is Gambang Kromong. The Provincial Government of DKI Jakarta with various other interests, then carried out cultural preservation through the Cultural Arts Training Center (PPSB). This study describes how the Gambang Kromong Training Program is organized by PPSB, through the ethnographic method which has been carried out since 2018, then by data collection techniques through observation, interviews, and literature review related to the research object. The results of the collected data are then analyzed through the perspective of the theory of cultural reproduction and the theory of hegemony. The PPSB Gambang Kromong Training Program in the 2016-2019 period has succeeded in forming an ideal cultural reproduction system. The stages of the program cover quite a lot of aspects and various factors that also support a cultural reproduction effort, especially for the Gambang Kromong traditional arts in DKI Jakarta. Unfortunately this program had to stop due to policies that forced restructuring. The role of PPSB, which is part of a political society, unfortunately has to lose in the hegemony game of the institution above it, and this also has an impact on civil society which includes art galleries, schools, traditional arts practitioners, and the Betawi community in general. Policies that show the government’s inconsistency in carrying out the preservation and reproduction of culture, eventually add to the question in terms of cultural programs to the interests of the institution alone.